1989
DOI: 10.1152/ajpendo.1989.256.5.e676
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic glucose production and insulin sensitivity preceding diabetes in monkeys

Abstract: The purpose of this study was to identify the relationship between basal hepatic glucose production (HGP) and peripheral insulin sensitivity as assessed by the hyperinsulinemic euglycemic clamp prior to and during the development of non-insulin-dependent (type 2) diabetes mellitus in rhesus monkeys. Twenty-six male monkeys (Macaca mulatta), including normal animals and monkeys in various phases of the development of spontaneous obesity-associated type 2 diabetes were studied. Fasting plasma glucose (FPG) and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 2 publications
7
73
0
Order By: Relevance
“…The situation is more complex following food ingestion when glucose appearance equals the sum of EGP and the rate of appearance of the ingested glucose (6). There is currently limited data as to the contribution of these processes to fasting hyperglycemia (7,8) and no data regarding the regulation of postprandial glucose metabolism in individuals with IFG. The latter is of particular interest since while most individuals with IFG also have either IGT or diabetes, some have normal glucose tolerance (NGT).…”
mentioning
confidence: 99%
“…The situation is more complex following food ingestion when glucose appearance equals the sum of EGP and the rate of appearance of the ingested glucose (6). There is currently limited data as to the contribution of these processes to fasting hyperglycemia (7,8) and no data regarding the regulation of postprandial glucose metabolism in individuals with IFG. The latter is of particular interest since while most individuals with IFG also have either IGT or diabetes, some have normal glucose tolerance (NGT).…”
mentioning
confidence: 99%
“…In addition, longitudinal studies in American Pima Indians (38,39), in rhesus monkeys (40), and recently in offspring of two diabetic parents (15,17) have demonstrated that insulin resistance precedes the development of frank NIDDM. These consistent findings in several independent population studies have led to the widespread view that genetically determined peripheral insulin resistance may be the primary underlying abnormality of glucose metabolism responsible for the development of NIDDM.…”
Section: Discussionmentioning
confidence: 99%
“…The spontaneously obese diabetic rhesus monkey is extraordinarily similar to human NIDDM with respect to its clinical presentation and underlying pathophysiology (29)(30)(31). When maintained in a protective environment and allowed ad lib.…”
Section: Introductionmentioning
confidence: 99%